A interação de atores nos conselhos gestores e a sua relação com coprodução de serviços públicos: uma revisão sistemática da literatura - Almeida, Thiago Chagas de (2021)
Co-production in public services is an emerging approach in the study of public policy, based on the conception that they are made up of different social actors. When perceiving a compatibility of this approach to the management councils, because they involve multiple actors in the elaboration of certain public policies, this Dissertation asked: how does the interaction of actors in the councils be associated with the co-production approach? Therefore, the objective of the research was to analyze the relationship between the co-production approach and the interaction of actors in the councils. As specific objectives, it was proposed to: Identify the characteristics of the studied councils that can influence co-production; Analyze the theoretical and practical evidence on this relationship; and Indicate the possibilities for future studies. For that, a systematic review of works voted on the subject was carried out, through qualitative meta-synthesis. Data analysis was performed using thematic content analysis technique. The results showed that management councils are spaces that are conducive to co-production, as they promote the interaction of actors to discuss certain public services. However, for coproduction to occur in this way, councilors have to influence the results of public policies in some way. The effectiveness of these mechanisms, consequently reaching coproduction, turns out to be a fundamental measure for the development of social participation and participatory democracy.